A study of meiosis and spermiogenesis in the testicular lobes of Antiteuchus tripterus (Heteroptera : Pentatomidae) - Souza, Herderson Vnicius de [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP]; Costa, Luiz Antonio Alves; Itoyama, Mary Massumi [UNESP] (Czech Acad Sci, Inst Entomology, 2007)
An analysis of testicular morphology and spermatogenesis in the Heteroptera species Antileuchus tripterus (Pentatomidae) revealed that these traits differ from that recorded for other species of the same family. The testes of A. tripterus have only six lobes, while other species of the same family typically have seven lobes, including a compound lobe, i.e., a lobe containing another in its lumen. A study of meiosis and sperm structure in the different lobes of A. tripterus revealed a conventional meiosis in the lobes numbered one to three. In lobe four, however, prophase I spermatocytes exhibit the morphological characteristics of the so called diffuse stage and are larger than those in lobes 1-3 in this and the remaining phases of meiosis. Thus, the resulting spermatids are not only larger but also their head is morphologically different. Lobe 5 exhibits characteristies known from other Pentatomidae species such as an uneven distribution of chromatin to the daughter cells, which give rise to cells of different sizes. This lobe forms spermatozoa of different sizes. Lobe 6, contained within lobe 5, differs from it by having larger cells at a stage similar to the so called diffuse and spermatid tails with cross divisions, which are not found in other lobes and unreported in the literature.
Keywords: Heteroptera; Pentatomidae; Meiosis; spermatozoa; testicular lobes; harlequin lobe